Dependence of shear wave seismoelectrics on soil textures: a numerical study in the vadose zone - Zyserman, Fabio I. (2017)
Fil: Zyserman, Fabio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina.